(untitled) (Journal of Asian Development Studies, 2026)
Fragility of national currencies belonging to “Fragile Five” countries has increased in the aftermath of the declaration of Federal Reserve about the end of Quantitative Easing program. The values of national currencies against U.S. dollar are depreciated. Both the structure of financial systems and absence of financial capital needed in the pathway to economic development are effective on exchange rates. In addition to economic developments after May 2013, Fragile Five economies achieved to reduce current account deficit in recent years. The situation with national currencies brings another question into mind if the depreciation in national currencies is effective on current account deficit. In this study, we aim to investigate the structure of relation between variables via SVAR analysis. Results show that most of the economies are gained from depreciation of national currencies. The depreciation of national currencies is not effective in South Africa and India. This result indicates that the structure of export is different in these countries.